Sistem Perpustakaan Terintegrasi - Yusniah Yusniah; Inggrid Masita Dewi; Tiara Rachellya; Nur Sawiyah Nasution (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Currently, libraries need to integrate so that they can take advantage of the technology that is currently available. The existence of technology will provide convenience in the process of using library techniques that are more structured in terms of ease of knowing how the existence of a library is needed by its users. The type of research that the author uses is descriptive qualitative with a literature study approach. The results obtained by the authors related to the research carried out is technology in the library. Libraries can take advantage of technology so that the process in the process is more systematic. Keywords: Library; Integration